2016
DOI: 10.1007/s10096-016-2776-8
|View full text |Cite
|
Sign up to set email alerts
|

Uropathogen distribution and antimicrobial susceptibility in uncomplicated cystitis in Belgium, a high antibiotics prescribing country: 20-year surveillance

Abstract: Treatment of cystitis in primary care is usually empirical, guided by the prior probability of causal pathogens and their susceptibility. To re-evaluate empirical treatment guidelines, the actual distribution and susceptibility of uropathogens was examined and compared with two previous surveys in Belgium over the past 20 years. Because of the alarming increase in carriage of extended-spectrum β-lactamase (ESBL)- and carbapenemase-producing Escherichia coli, this specific resistance was explored. From May 2014… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
32
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(36 citation statements)
references
References 26 publications
4
32
0
Order By: Relevance
“…This study is nested within an observational survey on uropathogens and their susceptibility pattern in 256 adult women with symptoms of uncomplicated UTI [4].…”
Section: Study Design and Populationmentioning
confidence: 99%
See 2 more Smart Citations
“…This study is nested within an observational survey on uropathogens and their susceptibility pattern in 256 adult women with symptoms of uncomplicated UTI [4].…”
Section: Study Design and Populationmentioning
confidence: 99%
“…Consecutive studies provide evidence to consider a 'low-count bacteriuria' as a positive result [11,12,14,15]. Yet, even at a lower threshold, one-quarter to onethird of the urine cultures remained negative [3,4], which made some authors question the presence of an infectious agent all together and even propose a psychosomatic explanation for the complaints [15]. This could not explain why even women with a negative culture seemed to benefit from antimicrobial therapy [16,17].…”
Section: Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…The bacterium Escherichia coli (E. coli) is by far the most common uropathogen in older adults [ 1 ]. Investigations in residents from long-term care facilities also revealed that the primary indication for antimicrobial (antibiotic) use is a urinary tract infection (UTI) [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…Most of the isolates from women with acute, uncomplicated UTIs (uUTIs) were fluoroquinolone susceptible, and extended-spectrum-β-lactamase (ESBL)-producing E. coli strains were almost absent (36). However, the prevalence of Enterobacteriaceae producing ESBLs of the TEM, SHV, and CTX-M types has increased significantly in patients with complicated UTIs (cUTIs) (713).…”
Section: Introductionmentioning
confidence: 99%